Wage Inequality and the Rise in Returns to Skill - Juhn, Chinhui; Murphy, Kevin M.; Pierce, Brooks (Journal of Political Economy, 1993)
Using data from the March Current Population Survey, we document an increase over the past 30 years in wage inequality for males. Between 1963 and 1989, real average weekly wages for the least skilled workers (as measured by the tenth percentile of the wage distribution) declined by about 5 percent, whereas wages for the most skilled workers (as measured by the ninetieth percentile of the wage distribution) rose by about 40 percent. We find that the trend toward increased wage inequality is apparent within narrowly defined education and labor market experience groups. Our interpretation is that much of the increase in wage inequality for males over the last 20 years is due to increased returns to the components of skill other than years of schooling and years of labor market experience. Our primary explanation for the general rise in returns to skill is that the demand for skill rose in the United States over this period.